Transformasi Digital dalam Perbankan: Peran E-Businees dalam Mewujudkan Green Banking - Putri Amelia; Muhamad Iqbal Fasa (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
Digital transformation in the banking sector has become a key factor in improving operational efficiency and environmental sustainability. E-business itself is a technology for the development of a company, both internally and externally. Green Banking translates as a bank's effort to prioritize the implementation of sustainability in credit or sales activities. The type of research used is a qualitative data method recorded in books, notes, and reports of previous research findings. The methods used in this study are description and analysis. The description method aims to explain the phenomena associated with the ontological approach in Islamic economics, while the analytical method is used to analyze the data and information obtained from these literature sources. This study discusses how e-business strategies are applied in banking to realize the principles of green banking, Including the use of financial technology (fintech), digital-based banking services, and automation of transaction processes. With a qualitative approach and literature studies, the results show that digital transformation not only improves the efficiency and convenience of banking services, but also contributes to reducing carbon footprint and supporting sustainability policies in the financial sector Therefore, the integration of e-business in banking is a strategic step in realizing a more environmentally friendly banking system.